Benchmarking small power energy consumption in office buildings in the United Kingdom: A review of data published in CIBSE Guide F. (February 2013) - Menezes, Anna Carolina; Cripps, Andrew; Buswell, Richard A; Bouchlaghem, Dino
CIBSE's Guide F is a widely recognised guidance document on energy efficiency in buildings, which includes energy consumption benchmarks for small power equipment in offices. In its recently published 3rd edition, existing power demand benchmarks for office equipment were revised to better represent appliances found in contemporary office buildings. Other key sources of data such as typical operating hours for equipment, however, have been omitted. This paper compares the benchmarks published in both the 2nd and 3rd editions of Guide F against a set of measurements of small power loads in a real UK office building. Load profiles for the monitored equipment are also presented to supplement the information included in the new Guide F. Practical application: With the increasing demand for more realistic predictions of operational energy use in buildings, small power should not be disregarded since it typically accounts for more than 20% of total energy used in offices. Furthermore, small power loads can have a significant impact on the cooling loads of a building. This paper reviews existing benchmarks, focusing on the new update to CIBSE Guide F, comparing available benchmarks against newly gathered monitored data. Detailed load profiles for individual office equipment are also provided, which can be used by designers to inform better predictions of small power consumption in office buildings.